2019
DOI: 10.1080/1359432x.2019.1588887
|View full text |Cite
|
Sign up to set email alerts
|

Work engagement interventions can be effective: a systematic review

Abstract: Work engagement is associated with important individual and organisational outcomes (e.g., employee health and well-being, performance). This narrative systematic review aims to synthesise the increasing number of work engagement interventions and inform future research by exploring: (1) the specific intervention foci, delivery methods and content of engagement interventions; (2) intervention effectiveness; and (3) underlying mediators and moderators. A systematic search for interventions employing a validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(124 citation statements)
references
References 111 publications
7
94
0
8
Order By: Relevance
“…Although these RCTs have been performed, there have been few systematic reviews and meta-analyses of them, and these treated only individual aspects of SWB. For example, Knight and his colleagues conducted a systematic review of interventions to increase hedonic well-being (e.g., work engagement) (Knight et al, 2017(Knight et al, , 2019. They reported that mindfulness could be useful (Knight et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these RCTs have been performed, there have been few systematic reviews and meta-analyses of them, and these treated only individual aspects of SWB. For example, Knight and his colleagues conducted a systematic review of interventions to increase hedonic well-being (e.g., work engagement) (Knight et al, 2017(Knight et al, , 2019. They reported that mindfulness could be useful (Knight et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Knight and his colleagues conducted a systematic review of interventions to increase hedonic well-being (e.g., work engagement) (Knight et al, 2017(Knight et al, , 2019. They reported that mindfulness could be useful (Knight et al, 2019). Next, Weiss et al (2016) reported a meta-analysis of RCTs of behavioral intervention on eudemonic well-being (e.g., psychological wellbeing), although it targeted the general population.…”
Section: Introductionmentioning
confidence: 99%
“…La revisión sistemática que planteamos en este protocolo pretende resolver (en una publicación futura) las siguientes preguntas inspiradas por la investigación de campo de los autores del trabajo y otras investigaciones publicadas (Knight et al, 2019;Patterson et al, 2010;Vidal-Carreras et al, 2015):…”
Section: Preguntas De Investigación a Resolver Con La Revisión Sistemunclassified
“…Partiendo del texto completo de los artículos elegibles, el cuarto autor extraerá la información etiquetando los fragmentos que representan a nuestras preguntas de investigación y rellenando una ficha de cada una de las referencias. Si no hay información se etiqueta como "no disponible" (Dogan & Unutulmaz, 2016;Knight et al, 2019;Lummus et al, 2006;Sanchez & Blanco, 2014;Vandborg et al, 2012):…”
Section: Interesanteunclassified
See 1 more Smart Citation